1996
DOI: 10.1128/mcb.16.8.4387
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Bud Emergence Gene BEM4 and Its Interactions with Rho-Type GTPases in Saccharomyces cerevisiae

Abstract: The Rho-type GTPase Cdc42p is required for cell polarization and bud emergence in Saccharomyces cerevisiae. To identify genes whose functions are linked to CDC42, we screened for (i) multicopy suppressors of a Ts ؊ cdc42 mutant, (ii) mutants that require multiple copies of CDC42 for survival, and (iii) mutations that display synthetic lethality with a partial-loss-of-function allele of CDC24, which encodes a guanine nucleotide exchange factor for Cdc42p. In all three screens, we identified a new gene, BEM4. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 55 publications
0
46
0
1
Order By: Relevance
“…Furthermore, similar results were ob served with the human RhoB and RhoC proteins (results not shown), a further indication that it may be a com mon pathway for all Rho-related proteins. In keeping with this notion, it has been reported that at least in S. ceievisiae, a single protein, designated as BEM4, can in teract physically with several members of the Rho fam ily including Rho and CDC42 proteins (Mack et al 1996), suggesting that different members of the Rho fam ily may share some of their effectors.…”
Section: Genes and Developmentmentioning
confidence: 84%
“…Furthermore, similar results were ob served with the human RhoB and RhoC proteins (results not shown), a further indication that it may be a com mon pathway for all Rho-related proteins. In keeping with this notion, it has been reported that at least in S. ceievisiae, a single protein, designated as BEM4, can in teract physically with several members of the Rho fam ily including Rho and CDC42 proteins (Mack et al 1996), suggesting that different members of the Rho fam ily may share some of their effectors.…”
Section: Genes and Developmentmentioning
confidence: 84%
“…Other Players BEM4 encodes a protein required for bud emergence at higher temperature (100). Because it interacts with constitutively active and dominant negative forms of Cdc42 as well as with Rho1, Rho2, and Rho4, its role in cell morphogenesis may be more general: e.g.…”
Section: Regulatorsmentioning
confidence: 99%
“…27 FET3 encodes an integral membrane multicopper oxidase, which mediates resistance to copper ion toxicity. 28,29 BEM4 codes for a protein involved both in the establishment of cell polarity and bud emergence, in Rho protein signal transduction, 30 and in maintenance of proper telomere length. 31 Finally, the products of the last two genes are involved in mitochondrial metabolism: CBP3 encodes a mitochondrial chaperone required for assembly of the cytochrome bc1 complex 32,33 whereas MRLP24 codes for a mitochondrial RP of the large subunit.…”
Section: The Cara Strain or How To Make Pol I Transcription Constitumentioning
confidence: 99%